Kasus-kontrol kejadian antraks di kabupaten Sumba Barat Daya - Marseni Banne Ringgi; Agnesia Endang Tri Hastuti Wahyuni; Setyawan Budiharta (Jurnal Sain Veteriner, 2011)
Problems of natural, technical and social nature are factors that explain the existence of anthrax in the District of Southwest Sumba (DSS).